Congo Red-based assay to quantify the modified Glucagon Like Peptide-1 Aggregation by Spectrophotometric Scanning Method - Venkata Sri Krishna Kona; Saida Lavudi (The Bioscan, 2024)
Aggregation of peptides that are of therapeutic importance when administered to patients leads to cytotoxic effect. Recently Glucagon-like peptide-1-based drug formulations are being prescribed to help alleviate Type-2 diabetes. Few studies reported this peptide tends to aggregate and form fibrils. Congo red is a histological stain known for its strong binding to β-sheet-rich fibrillar proteins, which results in a shift in its absorbance spectrum when it attaches to amyloid structures. This characteristic has been utilized in earlier research to investigate interactions with proteins such as insulin. In this study, we have developed a spectrophotometric assay specifically designed for quantifying aggregated forms of modified GLP-1 (mGLP) peptide. This method is straightforward and efficient, offering rapid results without the need for specialized equipment or costly reagents. Here CR–mGLP Spectrophotometric assay provides precise and cost- effective quantification by directly measuring aggregated mGLP in absolute terms, facilitating investigation of peptide aggregation and its implications in various biological and therapeutic applications.